Application of Survival Analysis and Multistate Modeling to Understand Animal Behavior: Examples from Guide Dogs - Asher, Lucy; Harvey, Naomi D.; Green, Martin; England, Gary C. W. (Frontiers in Veterinary Science, 2017)
Epidemiology is the study of patterns of health-related states or events in populations. Statistical models developed for epidemiology could be usefully applied to behavioural states or events. The aim of this study is to present the application of epidemiological statistics to understand animal behaviour where discrete outcomes are of interest, using data from guide dogs to illustrate. Specifically, survival analysis and multi-state modelling are applied to data on guide dogs comparing dogs that completed training and qualified as a guide dog, to those that were withdrawn from the training program. Survival analysis allows the time to (or between) a binary event(s) and the probability of the event occurring at or beyond a specified time point. Survival analysis, using a cox proportional hazards model, was used to examine the time taken to withdraw a dog from training. Sex, breed and other factors affected time to withdrawal. Bitches were withdrawn faster than dogs, Labradors were withdrawn faster, and Labrador x Golden Retrievers slower, than Golden Retriever x Labradors; and dogs not bred by Guide Dogs were withdrawn faster than those bred by Guide Dogs. Multistate Modelling (MSM) can be used as an extension of survival analysis to incorporate more than two discrete events or states. Multistate models were used to investigate transitions between states of training to qualification as a guide dog or behavioural withdrawal, and from qualification as a guide dog to behavioural withdrawal. Sex, breed (with purebred Labradors and Golden retrievers differing from F1 crosses) and bred by Guide Dogs or not, effected movements between states. We postulate that survival analysis and multistate modelling could be applied to a wide range of behavioural data and key examples are provided.